Adaptive Social Protection and Disaster Risk Management : A Case Study of Japan - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2020)
Japan has long suffered from intermittent but devastating natural disasters. Over the years, the country has developed a comprehensive disaster risk management (DRM) system to ensure that disaster response and recovery are as effective and efficient as possible. Japan has also created an elaborate system to provide social and economic assistance to disaster victims, including the most vulnerable. Today, Japan isa model of how the DRM and Adaptive Social Protection (ASP) systems can function in the context of rapid onset disasters, which, though infrequent, often have severe consequences. Japan is ranked fourth among the 171 countries most exposed to natural disasters (Bundnis Entwicklung Hilft 2017). Until the 1950s, such disasters frequently led to thousands of deaths. Since then, however, the number of deaths from these events has decreased markedly due to the improvement of the country’s DRM system. Nevertheless, mega-scale disasters, especially the ‘Great Hanshin-Awaji Earthquake Disaster’ in 1995 and the ‘Great East Japan Earthquake’ and tsunami in 2011, have still resulted in significant damage and loss of life. Given the high probability that a large-scale disaster could occur soon, Japan has continuously made efforts to further develop disaster risk mitigation and preparedness measures, often in response to a specific disaster for which aspects of the existing systems were found wanting.